Screening of actinobacteria isolated from rice and their potential to inhibit virulence of Xanthomonas oryzae pv. oryzae - ULVANA TRI NURWULAN; TRI JOKO; TRIWIDODO ARWIYANTO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nurwulan UT, Joko T, Arwiyanto T. 2025. Screening of actinobacteria isolated from rice and their potential to inhibit virulence of Xanthomonas oryzae pv. oryzae. Biodiversitas 26: 1424-1432. Xanthomonas oryzae pv. oryzae (Xoo), the pathogen causing bacterial leaf blight, is a major obstacle to improving rice productivity. The virulence factors of Xoo, such as motility, biofilm formation, and Extracellular Polysaccharides (EPS), are significant contributors to its pathogenicity. Actinobacteria, known for their beneficial properties, have promising applications in biological control. This study aimed to isolate actinobacteria and evaluate their potential to suppress Xoo virulence. Actinobacteria isolates were obtained from paddy fields in Yogyakarta, which have been proven to effectively inhibit the swimming, swarming, and twitching motility of Xoo. Isolates KpNg1 and Bs3 showed the most significant suppression, reducing motility to an average diameter of 0.2 cm. All actinobacteria isolates demonstrated the ability to inhibit biofilm formation, as indicated by reduced absorbance values in the crystal violet binding assay, with biofilm inhibitory rates ranging from 16% to 78%. Similarly, the EPS inhibition assay showed that all isolates significantly decreased EPS production, with inhibitory rates ranging from 4% to 49%. The inhibition of Xoo virulence factors is associated with quorum quenching mechanisms, particularly in relation to pili and flagella function. Isolates Bs1, KpS, and Bs3 were found to be closely related to Rhodococcus sovatensis by phylogenetic analysis based on 16S rRNA gene sequences. At the same time, isolates KpNg1, SGg, and Bs2 were found to be closely related to Rhodococcus yunnanensis. These findings underscore the intriguing role of actinobacteria in suppressing Xoo virulence, paving the way for further research and potential applications in biological control.